Walk'n'Talk: Effects of a communicative strategy - Heiner Böttger; Deborah Költzsch (Peoples' Friendship University of Russia (RUDN University), 2021)
The article focuses on the synergy effects of walking and talking simultaneously and the resulting conclusions on didactical practices regarding foreign language teaching. The study therefore consists of two different sections. On the one hand, the aim of this work is to conduct a cross-science analysis in order to transfer significant findings of the reference sciences, including neurobiology, to the field of foreign language didactics. On the other hand, task formats are developed on a methodological level that reflect a practical implementation of the previous finding. The aim of these transfer considerations is to make use of the biological predispositions in humans regarding movement and to apply them to communicative areas in foreign language teaching. As this research area is still mostly unexplored, the article functions as an exploratory approach to the matter as well as fundamental research work in order to generate new research questions and to expand the potential of the topic. It sets out to employ common neurobiological effects of Walk'n'Talk to create general as well as specific task formats, which in turn require future evaluations. Therefore, while the results of this work show potential opportunities within this context, they are equally limited due to the lack of a scientific basis. Going forward, this means that methodological testing of the aforementioned transfer efforts and task formats is necessary.